2007
DOI: 10.1016/j.ymben.2007.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of co-down-regulation of caspase-3 and caspase-7 by siRNAs on sodium butyrate-induced apoptotic cell death of Chinese hamster ovary cells producing thrombopoietin

Abstract: Previously, the expression of caspase-3 siRNA could not effectively inhibit sodium butyrate (NaBu)-induced apoptotic cell death of recombinant Chinese hamster ovary (rCHO) cells producing human thrombopoietin (hTPO). Caspase-3 siRNA expressing cells appeared to compensate for the lack of caspase-3 by increasing active caspase-7 levels. For the successful inhibition of NaBu-induced apoptosis of rCHO cells, both caspase-3 and caspase-7 were down-regulated using the siRNA expression vector system. Co-down-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 40 publications
4
42
0
Order By: Relevance
“…Protein quality has also been improved by using RNAi to suppress specific genes, resulting in both increased antibody-dependent cellular cytotoxicity for anticancer therapeutics Kanda et al, 2007;Mori et al, 2004), as well as higher sialic acid content in recombinant glycoproteins (Ngantung et al, 2006). Specific examples of antiapoptosis engineering involving RNAi include enhancing cell viability and protein production in CHO cells through the downregulation of either caspase-3 expression (Lai et al, 2004;Sung et al, 2005) or the expression of both caspase-3 and caspase-7 (Sung et al, 2007) as well as the suppression of the antiapoptotic genes Alg-2 and Requiem (Wong et al, 2006b). The latter study was the second article in a series that used transcriptional profiling to determine potential RNAi targets (Wong et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…Protein quality has also been improved by using RNAi to suppress specific genes, resulting in both increased antibody-dependent cellular cytotoxicity for anticancer therapeutics Kanda et al, 2007;Mori et al, 2004), as well as higher sialic acid content in recombinant glycoproteins (Ngantung et al, 2006). Specific examples of antiapoptosis engineering involving RNAi include enhancing cell viability and protein production in CHO cells through the downregulation of either caspase-3 expression (Lai et al, 2004;Sung et al, 2005) or the expression of both caspase-3 and caspase-7 (Sung et al, 2007) as well as the suppression of the antiapoptotic genes Alg-2 and Requiem (Wong et al, 2006b). The latter study was the second article in a series that used transcriptional profiling to determine potential RNAi targets (Wong et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…When Dual-10 cells were treated with 2.5 mM sodium butyrate, the mean cell number remained similar to the seeding density when compared to Dual-10 cells treated with vehicle, though no significant cell death was seen. The effect of butyrate on cell growth and apoptosis in CHO cells has previously been observed and strategies to improve cell growth are being considered, including media additives such as silk worm hemolymph, down-regulation of BAK, BAX, Caspase 3 and Caspase 7, and overexpression of bcl-2 (Cost et al 2010;Kim et al 2009;Sung et al 2007;Choi et al 2005b;Lee 2002, 2000).…”
Section: Screening Of Cell Linesmentioning
confidence: 99%
“…Cells were washed with ice-cold phosphate-buffered saline (PBS) and lysed in a fresh lysis buffer (1% Nonidet P-40, 0.1% sodium dodecylsulfate [SDS], 0.02% NaN 3 , 50 mM Tris-Cl [pH 8.0], 150 mM NaCl and protease inhibitors [Roche]), as described previously (Hwang and Lee, 2008b;Sung et al, 2007). Approximately, 20 mg of protein extract was loaded after measurement by the Bio-Rad protein assay, as described by the manufacturer's protocol (Bio-Rad, Hercules, CA).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Until now, apoptosis in rCHO cell culture has been recognized as an important task to be solved, and therefore, there have been numerous studies focusing on the onset of apoptosis and anti-apoptotic gene engineering in rCHO cells (Arden and Betenbaugh, 2004). As a result, it was found that the onset of apoptosis in rCHO cells can be delayed by promoting anti-apoptotic factors as well as by inhibiting the expression of pro-apoptotic factors (Chiang and Sisk, 2005;Figueroa et al, 2007;Kim and Lee, 2000;Lim et al, 2006;Sauerwald et al, 2003;Sung et al, 2007;Tey et al, 2000;Wong et al, 2006;Yun et al, 2007).…”
Section: Introductionmentioning
confidence: 99%